Papel da PI3K8 no controle da contratilidade vascular no Diabetes Mellitus I: estudo funcional e eletrofisiológico - Jose Felippe Pinho da Silva (2012)
Diabetes is associated to damage in several organs and systems including the vascular system. Vascular diseases are the main cause of mortality and morbidity in diabetes patients. However, the mechanisms that determine vascular modifications on diabetes disease are unclear. Our main goal was to investigate signaling pathways involved in vascular dysfunction in a murine model of streptozotocin-induced diabetes type I. Method: The thoracic aorta of C57BL/6 mice was isolated, cut in rings and mounted in a myograph. Vascular studies were performed using isometric transducers in an organ bath system. Calcium currents were recorded by patch-clamp technique (in whole cell configuration) from aorta cells freshly dissociated. Protein expression was mesuared by western blot technique. Antisense oligonucleotides were used to knockdown PI3K expression. Results: there was no difference in the vasorelaxation response of control and diabetic animals aorta. However, aorta from diabetic animals showed a higher contractility in the presence of phenylephrine or KCl. Western blot data also demonstrated an increased expression of L-type voltage-gated calcium channels (Cav1.2), PI3K and Rho on aorta from diabetic animals. In the diabetic animal treated with antisense for PI3K, the expression of Cav1.2 and Rho was normalized. Both PI3K pharmacological inhibition and the administration of oligodeoxinucleotides antisense against PI3K recovered Cav1.2 current densities to the same level as control animals. Also, Rho inhibitiors, fasudil (10 uMol/L) and Y27632 (5 uMol/L), normalized Cav1.2 calcium currents in diabetic animals. The inhibition of PI3K and Rho did not have additive effect. Surprisingly, althought nifedipine, a Cav1.2 blocker, had the highest inhibitory effect over aorta cells of diabetic animals it still could not recover the contractile response to the same level as control animals. These results suggest that the increased calcium influx throught Cav1.2 channels is not the only mechanism responsible for the diabetic animals increased vascular contractility. Furthermore, the activation of Cav1.2 channels, PI3K and Rho may also act in a different pathway to control the contractile response. Both pharmacological and antisense inhibition of PI3K normalized the contractile response on diabetic animals suggesting that all the mechanisms involved on the regulation of the contractility on diabetic animals are related to PI3K activity. The Y27632 (inhibition of Rho) abollished the contractile response either on diabetic or control animals demonstrating the fundamental role of this pathway in the contractile control aorta from mice. Conclusions and implications: our results showed that diabetes type 1 induced by STZ occurs by a remodeling process of the molecular mechanisms involving the contractile response control in smooth muscle from aorta , including the increase in expression of PI3K, Cav1.2 and Rho. On diabetic animals, PI3K activates the Rho/RhoK pathway inducing an increase in calcium currents through Cav1.2 channels and increase the phosphorilation level of the contractile filaments. Therefore, the PI3K inhibition can represent a new therapeutic target for the treatment of vascular dysfunction in diabetic patients.